Tantangan Nigeria Dalam Mencapai Poin 6 SDGs (Air Bersih dan Sanitasi Layak): Studi Kasus Pencemaran Lingkungan Delta Niger oleh Shell Company - Tri Utami, Arum; Ardyanti, Moza (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
Environmental pollution is one of the key issues that is a major concern in the Sustainable Development Goals (SDGs). One country that remains actively engaged in achieving the SDGs is Nigeria, which continues to face environmental pollution challenges, particularly in the Niger Delta region, where environmental degradation has resulted from oil mining activities by Shell Company. The impact of these mining activities has significantly affected water cleanliness in the Niger Delta, which aligns with SDG Goal 6, focusing on water sanitation. This case study highlights the environmental pollution caused by Shell’s oil extraction activities in the Niger Delta and how this has become a major obstacle in achieving SDG Goal 6: "Clean Water and Sanitation", using ecological security theory. By applying ecological security theory, this study demonstrates that environmental degradation not only threatens public health and livelihoods but also exacerbates social injustice and conflict. Through a collaborative and comprehensive approach, this article recommends the active involvement of all stakeholders to achieve SDG Goal 6 in a sustainable manner. The findings emphasize the importance of integrating ecological security principles into efforts for resource recovery and management in Nigeria.